Review Of Law and Human Rights On The Practice Of Impunity For Performers Of Gross Human Rights Violation In Indonesia - Moeltazam, Moeltazam; Daming, Saharuddin; Al Afghani, M. Mova (JURNAL MAHASISWA YUSTISI, 2024)
The text discusses the practice of impunity for perpetrators of serious human rights violations in Indonesia, including the causal factors, the state's strategy in overcoming impunity, as well as supporting and inhibiting factors for law enforcement. This research aims to analyze the factors that cause impunity, state strategies in overcoming impunity, and propose legal reforms to eliminate impunity. With a framework based on Fraser Douglas' theory regarding state responsibility in upholding the law, this research highlights challenges such as unfulfilled justice, divided international attention, and the lack of mechanisms between countries in the ASEAN region. Lack of adequate laws, unequal punishment, corruption in law enforcement officials, and socio-cultural factors are also the focus of discussion. Reform efforts are needed in the justice and law enforcement systems, including increased education, training, support, protection, as well as adequate resource allocation. The political, social and legal implications of the law enforcement process for serious human rights violations in Indonesia are also explained in this text. With recommendations to strengthen the legal system, the role of Komnas HAM, international support, and political reform, it is hoped that law enforcement against serious human rights violations can be improved in Indonesia.